Pemberdayaan Masyarakat Melalui Pemanfaatan Tanaman Obat Keluarga (Toga) Berbasis Pastisipasi di Desa Sumberkalong, Kabupaten Bondowoso - Siti Rahmatillah N.S; Nova Abil Isfian; Ibnatus Syarifah; Mohammad Alvan Fahmi; Syarif Hidayatulloh; Anik Maghfiroh; Sania Wahyu Ningrum; Nadiya Khilmiyaturrosikнон (Lembaga Pengembangan Kinerja Dosen, 2025)
The community in Sumberkalong Village, Wonosari District, Bondowoso Regency faces several issues related to the use of Family Medicinal Plants (TOGA), including lack of knowledge, underutilized home gardens, and the absence of active community groups managing TOGA. A participatory approach is needed to address these issues sustainably. This community service activity aims to improve public knowledge and skills regarding the cultivation and utilization of TOGA, promote the optimal use of home gardens, and establish community-based TOGA activist groups. The method used is Participatory Action Research (PAR) through stages of problem identification, participatory planning, collaborative implementation, observation, reflection, and follow-up actions. The results show increased public awareness and enthusiasm in cultivating TOGA, the formation of small TOGA groups, and program sustainability through cooperation between residents and local health cadres.